2022
DOI: 10.3390/s22218357
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of FeNi Films and FeNi-Based Trilayers with Out-of-Plane Magnetization Component

Abstract: FeNi films of different thickness and FeNi/(Fe, Co)/FeNi trilayers were prepared by magnetron sputtering deposition onto glass substrates. The permalloy films had a columnar microstructure. The detailed analysis of the magnetic properties based on the magnetic and magneto-optical measurements showed that at thicknesses exceeding a certain critical thickness, hysteresis loops acquire a specific shape and the coercive force of the films increase sharply. The possibility of the estimation of the perpendicular mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Considering our results and literature previously published in electrodeposited and sputtered Ni-Fe alloys [17,[27][28][29], we can correlate the existence of stripe domains to the columnar growth. Moreover, our results indicate that in the considered as 'thick' thickness regime, equal or above 800 nm, stripe domains are not affected by a perpendicular magnetic field applied during growth.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Considering our results and literature previously published in electrodeposited and sputtered Ni-Fe alloys [17,[27][28][29], we can correlate the existence of stripe domains to the columnar growth. Moreover, our results indicate that in the considered as 'thick' thickness regime, equal or above 800 nm, stripe domains are not affected by a perpendicular magnetic field applied during growth.…”
Section: Resultssupporting
confidence: 80%
“…The existence of some remanence in the OOP loops might be understood considering that the studied samples do not completely fulfill the requirement of the Murayama's model [26], that it is generally used to understand the formation of stripe domains. In that model, it is needed that the magnetization is aligned in the direction parallel to the stripes [26][27]. In the studied samples, some magnetization component misaligned with respect to the stripes direction can promote the observed remanence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of efficient magnetization switching and low gilbert damping are intricately linked to alloy composition, deposition method, substrate material, doping, , film thickness and annealing conditions [11,13,[24][25][26][27][28][29]. For electronics applications like high-frequency microwave filters and inductors, thicker films are preferred due to their enhanced performance characteristics [30]. Most of the research on permalloy has focused on less than 100 nm thick films which can be easily deposited using sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, interfaces in multilayers are sources of the internal deformations, which should result in a shift of the critical thickness due to the magnetoelastic contribution to the perpendicular magnetic anisotropy of the films, as well as due to the influence of the interface to the layer growth mode. For single permalloy layers prepared by magnetron sputtering, it was shown that the constant of perpendicular magnetic anisotropy is the thickness invariant [31]. In a multilayered structure, the numerous interfaces may result in an increase in the value of the perpendicular magnetic anisotropy energy.…”
Section: Introductionmentioning
confidence: 99%